Ejecución de un examen especial de las cuentas por cobrar de la empresa Cotisa S.A. - Armijos Contreras, Mayra Alexandra (My University, 2018)
The present investigation, is directed to conceptualize and analyze the application of special examination in the company ROUTES COTISA S.A. and the impact it has on internal control and accounting of accounts receivable, for which procedures defined in the implementation phase of the audit, as well as the preparation of the planning of the special examination, also, it is important to mention that the successful implementation of the same is given by the of application, which in the present case are the NIA 300 that makes references to the responsibility of the auditor in front of the planning and of the NIA 402 responsibility in the evidence obtained, to more than this was conducive to define the NAGAS as A medium that ensures the information obtained and issued by the auditor. In the case of the development of the research paper, consideration was given to the bibliographic-documentary methodology, that is to say, affection a thorough selection of file information, articles and regulations, which made it possible to carry out an inquiry with reasonable results and credible. It is important to mention that any company in particular the commercial character, must be aware of how essential it is to carry out an internal control of the appropriations allocated, since that will minimize potential risks in the accounts receivable and therefore in its liquidity and operationalization, hence, it is advisable to make use of the special examination through an internal audit, which empowers the administrator to know the problems and in turn be able to minimize in the times just in an optimal way.
La presente investigación, está dirigida a conceptualizar y analizar la aplicación del examen especial en la empresa RUTAS COTISA S.A. y el impacto que tiene en el control interno y contable de las cuentas por cobrar, para lo cual se definió procedimientos en la fase de ejecución de la auditoria, como también la preparación de la planificación del examen especial, asimismo, es importante mencionar que el éxito de la ejecución del mismo está dado por las nomas de aplicación, que en el caso presente son la NIA 300 que hace referencias a la responsabilidad del auditor frente a la planificación y de la NIA 402 responsabilidad en la evidencia obtenida, a más de ello fue propicio definir las NAGAS como un medio que garantiza la información obtenida y emitida por el auditor. Para el caso del desarrollo del documento de investigación, se tomó en consideración la metodología bibliográfica-documental, es decir, se llevó a afecto una minuciosa selección de información de archivos, artículos y reglamentos, lo cual permitió llevar a efecto una indagación óptima con resultados razonables y creíbles. Es importante mencionar que toda empresa en especial la de carácter comercial, deben estar consciente de lo fundamental que es llevar a cabo un control interno de los créditos asignados, ya que con ello minimizaran posibles riesgos en las cuentas por cobrar y por ende en su liquidez y operacionalización, de ahí que, es recomendable hacer uso del examen especial, mismo que faculta al administrador conocer los problemas y minimizarlos.
Keywords: EXAMEN ESPECIAL; CUENTAS POR COBRAR; AUDITORIA; NIA; NAGAS